Platelets in cancer and thrombosis - Riedl, J.; Pabinger, I.; Ay, C. (Hämostaseologie, 2014)
Platelets are the smallest circulating blood cells and their major function is the maintenance of haemostasis. They do not have a nucleus, but instead a multitude of granules that contain molecules important for several physiological processes. These granules can be released after platelet activation and thereby platelets take part in haemostasis, wound repair or immunological processes. Furthermore, platelets are also involved in the pathophysiology of several diseases, including cancer. Platelets can support various steps of cancer development and progression by promoting tumour growth, angiogenesis and metastasis. Moreover, platelets contribute to the hypercoagulable state frequently observed in cancer patients, leading to an increased risk of venous thromboembolism (VTE). In previous studies a high platelet count was repeatedly found to be associated with an elevated risk of VTE and a worse prognosis in patients with cancer.The aim of this review is to give an overview of the most important alterations of platelet physiology in cancer patients and how these alterations may influence cancer disease and contribute to cancer-associated VTE.
Keywords: Platelets; cancer; venous thromboembolism